2019
DOI: 10.1055/a-0828-7968
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects in the Diagnosis and Therapy of Fetal Hypoplastic Left Heart Syndrome

Abstract: Fetal hypoplastic left heart syndrome (HLHS) is a severe congenital heart disease with a lethal prognosis without postnatal therapeutic intervention or surgery. The aim of this article is to give a brief overview of new findings in the field of prenatal diagnosis and the therapy of HLHS. As cardiac output in HLHS children depends on the right ventricle (RV), prenatal assessment of fetal RV function is of interest to predict poor functional RV status before the RV becomes the systemic ventricle. Prenatal cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…Fetal therapy, including surgery and catheterization, is now available and practical for a number of conditions. MO has been applied as both a prognostic and therapeutic tool in fetuses with CHD, especially in those with hypoplastic growth of left heart structures [47].…”
Section: Congenital Heart Disease (Chd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal therapy, including surgery and catheterization, is now available and practical for a number of conditions. MO has been applied as both a prognostic and therapeutic tool in fetuses with CHD, especially in those with hypoplastic growth of left heart structures [47].…”
Section: Congenital Heart Disease (Chd)mentioning
confidence: 99%
“…However, the associated neural system retardation and abnormalities have become major concerns for these children. Although there is limited evidence, MO may offer prenatal protection from brain injury based on the relationship between reduced fetal cerebral oxygen consumption and impaired neurodevelopment [49], as well as the sO 2 of UV [47], in fetuses with CHD during short-term oxygen inspiration. Szwast et al have published the only study on the cerebral hemodynamic response to MO [50].…”
Section: Congenital Heart Disease (Chd)mentioning
confidence: 99%
“…63 Therefore, an additional thorough assessment of pulmonary venous (PV) Doppler (PVD) with a forward/reverse velocity-time integral (VTI) ratio of <3 has been found to be the strongest predictor of postnatal hemodynamic stability and the need for fetal intervention. 64 Despite a trend toward improved preoperative morbidity in neonates with a prenatal diagnosis of HLH, a recent systematic review revealed no significant impact on preoperative or postoperative Stage I mortality. 65 According to recent data from Richard et al, frequent serial fetal echocardiograms may not necessarily be needed to predict the need for an unexpected, emergent procedure.…”
Section: Hyp Opl a S Tic Lef T He Artmentioning
confidence: 99%
“…Jadcak et al stated that an early appearance and a longer presence of FO obstruction rather than the extent of obstruction are associated with an increase in short‐term mortality 63 . Therefore, an additional thorough assessment of pulmonary venous (PV) Doppler (PVD) with a forward/reverse velocity‐time integral (VTI) ratio of <3 has been found to be the strongest predictor of postnatal hemodynamic stability and the need for fetal intervention 64 . Despite a trend toward improved preoperative morbidity in neonates with a prenatal diagnosis of HLH, a recent systematic review revealed no significant impact on preoperative or postoperative Stage I mortality 65 .…”
Section: Hypoplastic Left Heartmentioning
confidence: 99%
“…1 These structures include the mitral valve, left ventricle (LV), aortic valve, ascending aorta, and aortic arch. [2][3][4][5][6][7] Obstruction can occur at various levels of LV inflow or outflow tracks. 3,6 Outflow obstructions arise through aortic valve atresia or stenosis and are the most common cause of underdevelopment of the LV.…”
mentioning
confidence: 99%